(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Varicose veins, which are easily identifiable, are veins in the subcutaneous tissues of the legs that are swollen, twisted, widening, twisting, and swelling. The inability of the valves to close properly usually results in blood reflux, which can induce symptoms of venous hypertension. The two saphenous junctions are generally considered to be the source of main varicose veins. These are the deep veins (small saphenous) in the legs and the superficial vein (bigger sephonous) that spreads retrogradely along the saphenous trunks to tributaries. Symptoms related to their lower limbs, including cramps, tingling, heaviness, swelling, and discomfort, pain, eczema. Methodology: The terms "varicose veins in lower extremities","duplex ultrasonography of varicose veins," and "pathogenesis of varicose veins" were used in the search. This evaluation only includes studies that demonstrate the utility of Doppler US in diagnosing varicose vein involvement patterns. Out of all the publications we found, only eighteen meet the inclusion criteria to be included in this review article. Diversity across research was found. Probably as a result of advancements in US technology and diagnostic methods, the accuracy of US in determining the pattern of varicose vein involvement grew with time. Based on the examined study. Objective: To evaluate the pattern of involvement of varicose veins by color Doppler. Data analysis: Data was analyzed by IBM SPSS software version 26. Conclusion: Our research topic is evaluation of pattern of involvement of varicose veins by color Doppler. The sample size of our study is 65 patients. We collected data from DHQ hospital, Madinah Teaching Hospital, Al Noor hospital. Out of which 47 were male and 18 were female. The most common cause of varicosities was long term standing occupations like, it effects mostly teachers, shopkeepers, bank managers, security guards. The effected veins were Great saphnous vein, Short saphnous vein and junctions were Saphnopopliteal, Saphnofemoral junction. The left leg was mostly effected than right leg and both legs were affected in fewer patients. There are different grades of reflux from grade I-IV occur in saphnopopliteal and saphnofemoral junction.